Komunikasi Pemerintah Desa Bantar Panjang dalam Memanfaatkan Website : (Studi Kasus di Desa Bantar Panjang Kec. Cikeusal Kab. Serang) - Ajat Sudrajat; Rd Nia Kania; Ail Muldi (Lembaga Pengembangan Kinerja Dosen, 2025)
The utilization of the village website as a medium of communication with the local community supports an effective service process for the community and village government officials. However, there are obstacles in the utilization of the village website in Bantar Panjang Village Government, Cikeusal Sub-district, such as limited human resources with only one website operator, lack of public knowledge about the website, and the need for training to improve operator skills. The objectives of this study are: 1) Knowing the management of the Bantar Panjang Village website in Cikeusal Sub-district, 2) Knowing the benefits of the village website for the Bantar Panjang Government, Cikeusal District. The research method used is qualitative. The results showed: 1) Website management is carried out by all village government officials in general and specifically handled by the village website operator. In its management, there are still obstacles, including an insufficient village budget for adding features and website maintenance. 2) Utilization of the village website is carried out by all parties of Bantar Panjang Village in accordance with their main duties and functions to present data on the village website. The conclusion of this research is that the communication carried out by the Bantar Panjang Village government in utilizing the village website is beneficial to the village government.